Impact of Occupational Safety and Health (K3) and compensation on employee performance: The role of organizational commitment - Amalia, Alifa Rizki; Azra, Firman El Amny; Suhendra, Suhendra (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
The purpose of this research is to analyze the impact of occupational safety and health (K3) and compensation with organizational commitment as mediation variable on employee performance. The study was conducted on contract daily employees at Dr. Suyoto Hospital Rehabilitation Center of the Ministry of Defense, Jakarta. This study used a quantitative sample of 68 employees using probability sampling technique. The data analysis technique used is path analysis using SPSS 29 software. The analysis used in this study includes validity test, reliability test, normality test, coefficient of determination test, f test, t test, and Sobel test to determine the mediating effect. The results of the study show that OSH (K3), compensation and organizational commitment have an effect on performance.